Praktek Sanitasi Higiene pada Usaha Pengolahan Dangke Susu Sapi di Kabupaten Enrekang, Sulawesi Selatan (THE PRACTICES OF HYGIENIC SANITATION IN PROCESSING INDUSTRIES OF COW MILK DANGKE IN ENREKANG DISTRICT, SOUTH SULAWESI) - Hatta, Wahniyathi; Sudarwanto, Mirnawati Bachrum; Sudirman, Idwan; Malaka, Ratmawati (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
Lack of hygienic sanitation conditions in food processing industry could contribute to the food safety.The aim of this study was to assess the implementation of hygienic sanitation practices in the processingindustries of cow milk dangke in Enrekang District, South Sulawesi. Total of 60 respondents wereinterviewed using questionnaire and observation on hygienic sanitation practices was carried out usingcheck-list.  Respondents were producers and also workers in the processing units in Cendana Sub-district,Enrekang which had been selected with simple random sampling technique.  Scoring of hygienic sanitationcondition were based on the application of hygienic sanitation practices on the checklist.  None of workerswore special clothes, put dangke molds in closed container, and wiped packaging of dangke with specialclothes.  Less than 50% of the workers  wore a head coverings, prepared papaya latex with boiled water,and covered dangke when molding.  A total of 50% of the workers immediately washed the molds afterused.  More than 50% of the workers washed their hands with soap before dangke processing, washed themolds with soap, wiped the packagings with a cloth before it used, stored the milk in a closed container,and cleaned papaya fruit before preparing papaya latex.  All of the workers made dangke while doinghousework. Hygienic sanitation condition of dangke processing industries that had good category was 3%while another 57% in moderate category and poor category was 40%.  The hygienic sanitation practices hadnot been fully implemented on the processing industries of cow milk dangke in Enrekang district, which ledto the category of hygienic sanitation condition of largely of them was moderate .
Keywords: Cow milk dangke, Practices, Hygienic sanitation, Processing industry, Enrekang